A Note on the Fractional Generalized Higher Order KdV Equation - Yongyi Gu (Journal of Function Spaces)
We obtain exact solutions to the fractional generalized higher order Korteweg-de Vries (KdV) equation using the complex method. It has showed that the applied method is very useful and is practically well suited for the nonlinear differential equations, those arising in mathematical physics.